Performance Analysis for Real Time Application Over LTE Network - Monika; Nandal, Deepak (International Journal of Computer Sciences and Engineering, 2025)
Packet Scheduling in LTE network is the fundamental task on which the performance of LTE network depends. Scheduling is a process to allocate the resources to users. Radio resource management is used for resource allocation. Many scheduling algorithms have been designed and proposed for scheduling. Scheduling is performed in both direction uplink and downlink. The main aim of this paper is to analyze the performance of downlink scheduling algorithms for real time flow. Three schedulers,i.e, Modified Largest Weight Delay First , Exponential Proportional Fairness, and Proportional Fairness are used for scheduling for real time flow VIDEO and non real time flow VOIP. The performance of schedulers is analyzed in terms of packet loss ratio, throughput and delay parameters. The result shows that performances of PF scheduler are not appropriate for real time application